Increased contribution of KCa channels to muscle contraction induced vascular and blood flow responses in sedentary and exercise trained ZFDM rats. (24th May 2022) - Sonobe, Takashi; Tsuchimochi, Hirotsugu; Maeda, Hisashi; Pearson, James T.
Abstract : Abstract: In resistance arteries, endothelium‐dependent hyperpolarization (EDH)‐mediated vasodilatation is depressed in diabetes. We hypothesized that downregulation of KCa channel derived EDH reduces exercise‐induced vasodilatation and blood flow redistribution in diabetes. To test this hypothesis, we evaluated vascular function in response to hindlimb muscle contraction, and the contribution of KCa channels in anaesthetised ZFDM, metabolic disease rats with type 2 diabetes. We also tested whether exercise training ameliorated the vascular response. Using in vivo microangiography, the hindlimb vasculature was visualized before and after rhythmic muscle contraction (0.5 s tetanus every 3 s, 20 times) evoked by sciatic nerve stimulation (40 Hz). Femoral blood flow of the contracting hindlimb was simultaneously measured by an ultrasonic flowmeter. The contribution of KCa channels was investigated in the presence and absence of apamin and charybdotoxin. We found that vascular and blood flow responses to muscle contraction were significantly impaired at the level of small artery segments in ZFDM fa/fa rats compared to its lean control fa/+ rats. The contribution of KCa channels was also smaller in fa/fa than in fa/+ rats. Low‐intensity exercise training for 12 weeks in fa/fa rats demonstrated minor changes in the vascular and blood flow response to muscle contraction. However, the KCa‐derived component in the response to muscle contraction was much greater in exercise trained than in sedentary fa/fa rats. These data suggest that exercise training increases the contribution of KCa channels among endothelium‐dependent vasodilatory mechanisms to maintain vascular and blood flow responses to muscle contraction in this metabolic disease rat model. Key points: Microvascular dysfunction in type 2 diabetes impairs blood flow redistribution during exercise and limits the performance of skeletal muscle and may cause early fatigability. Endothelium‐dependent hyperpolarization (EDH), which mediates vasodilatation in resistance arteries, is known to be depressed in animals with diabetes. Here, we report that low‐intensity exercise training in ZFDM rats increased the KCa channel‐derived component in the vasodilator responses to muscle contraction compared to that in sedentary rats, partly as a result of the increase in KCNN3 expression. These results suggest that low‐intensity exercise training improves blood flow redistribution in contracting skeletal muscle in metabolic disease with diabetes via upregulation of EDH. Abstract : Abstract figure legend Low‐intensity exercise training in ZFDM, metabolic disease rats with type 2 diabetes increases the KCa channel‐derived component of endothelium‐dependent hyperpolarization in the vascular and blood flow responses to skeletal muscle contraction compared to the responses in sedentary rats, partly due to upregulation of KCNN3 protein expression.